Comparative Study on Thermal Analysis of Flat Face and Curved Face FDM Printed Micro-Channel Fin Holders - Dharmendra Singh Rajput (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This work describes the use of deposition-based additive manufacturing (AM) techniques to fabricate heat exchangers. The paper study focused on a Heating, Ventilation and Air Conditioning of automobile application and used an industry-standard copper/aluminum heat exchanger manufactured with conventional technology as the basis for assessing performance. Conventional methods of producing micro-scale components for water cooling applications such as micro fluidic devices are limited to relatively simple geometries and are inefficient for prototype production. Rapid prototyping techniques may be applied to overcome these limitations. Fused Deposition Modeling is one such rapid prototyping process, which can build parts using layer by layer deposition technique with layers as low as 0.178 mm thick and using a select group of thermoplastic building materials. This paper presents the potential of Fused Deposition Modeling (FDM) system, in building prototypes of scaled micro-channels for experimental study of cooling capacity of water-cooling heat exchanger, scope and application of FDM system as a powerful and flexible rapid prototyping device is described. Micro channels of staggered shape are produced in ABS material on the UP-mini rapid prototyping system and a methodology is presented for thermal analysis study performance of the heat exchanger and its comparison to the conventional flat fin configuration.